Digital Twins. HBIM information repositories to centralize knowledge and interdisciplinary management of architectural heritage - Luis Cortés Meseguer; Jorge García Valldecabres (Vitruvio: International Journal of Architectural Technology and Sustainability)
It is obvious that the primary document will always be the building itself, but within the field of conservation, restoration or maintenance it is necessary to have a large documentary archive where the interventions are recorded. The older the monument is, the greater the knowledge of the built element must be before any intervention and this requires a lot of time in prior research and which can develop prior studies, in addition to the economic cost that it entails. This is why with the advancement of technology and digital repositories, digital platforms can be created within Heritage Building Information Modeling (HBIM). This article reflects the experience of an eight-century-old monument, San Juan of Hospital of Valencia (Spain), in which a virtual twin has been made with software and specific web platforms in facility management such as Archibus©, EcoDomus©, Zutec© that allow the integration of information from BIM models and data acquired through sensors. With this work, although it is economically expensive and requires a lot of time for people specialized in the required programs, is improving the efficiency of facility management. and maintenance planning for large buildings and infrastructure.